Analisis Gizi Rumput Laut Anggur (Caulerpa Racemosa) Subsitusi Ikan Layang (Decapterus Ruselli) Sebagai Alternatif Perbaikan Gizi Masyarakat - Damayati, Dwi Santy; Ibrahim, Irviani; Haris, Widya Astuti Haris; Habibi, Habibi; Alam, Syamsul (Al GIZZAI: PUBLIC HEALTH NUTRITION JOURNAL, 2024)
South Sulawesi is the province with the highest production of seaweed, and flying fish is a pelagic fishery resource with significant economic value, contributing predominantly to fisheries production. Both seaweed and flying fish have excellent nutritional value. This research aims to determine the nutritional content of Lawi-lawi seaweed meatballs with flying fish substitution. The method used involves comparing various formulations of Lawi-lawi seaweed and flying fish ratios, namely 100:0, 75:25, 50:50, 25:75, 0:100. The research results reveal the highest carbohydrate content in formula 2 (75:25) at 29.91%, the highest protein content in treatment 0:100 at 20.31%, the highest fat content in formula 3 (50:50) at 11.08%, the highest water content in formula 1 (100:0) at 52.5%, and the highest iron content in formula 3 (50:50) at 24.7860 mg/kg. The Anova test results indicate a significant difference among various formulations in the nutritional content of protein, fat, water, and iron, but there is no significant difference in carbohydrate content. Based on organoleptic hedonic quality tests, Lawi-lawi seaweed meatballs with flying fish substitution are best in formula 4 (25:75) based on color, aroma, texture, and taste. This research concludes that formula 4 (25:75) is the preferred organoleptic formulation, being the most liked formulation. It is recommended to undertake various food diversifications to enhance public interest in consuming good and nutritious food, thereby improving the nutritional status of the community using local food ingredients